Targeting the membrane-proximal domain of CD33 to maximize the efficacy of natural killer cell-based immunotherapies - Sheryl Y. T. Lim; Frances M. Cole; George S. Laszlo; Margaret C. Lunn-Halbert; Jenny Huo; Junyang Li; Allie R. Kehret; Roland B. Walter (Haematologica)
Not available.